Pengaplikasian Dry Ice Untuk Pengendalian Cylas formicarius pada Ubi Ketela Rambat - Afni Kurnia Firmani; Subagiya Subagiya; Ato Sulistyo (Universitas Sebelas Maret, 2018)
Cylas formicarius is the main pest of sweet potatoes especially in storage. Damage from the pest attacks can reduce yields up to 97% and even minor damage causes sweet potatoes cannot be consumed because they taste bitter and toxic. Warehouse pest control such as C. formicarius is generally carried out by fumigation. Dry ice is a solid CO₂ that can be used as a fumigant to control warehouse pests. This study aims to determine the application of dry ice as fumigant and different storage places for C. formicaius in sweet potatoes. The variables observed C. formicarius population and mortality, weight loss, decrease in water content, level of damage to sweet potatoes and taste testing. The results showed that the population of C. formicarius in control higher than the other treatments, in the storage area in the population space C. formicarius is higher than in dark storage. Mortality in the treatment of giving dry ice reached 100% at the dose of 5g, 10g and 15g. Weight reduction and decrease in water content in sweet potatoes correlate with each other where in the control treatment changes in weight and water content are highest compared to other treatments. Storage places have no effect on weight loss and loss of water content in sweet potatoes. Taste of sweet potatoes before and after the shelf life with the dry ice application has not changed.